(untitled) (Global Journal of Computer Science and Technology, 2013)
In order for the initial result of this research to be obtained scientifically, a decision was made on setting the limits of the universe of users to be studied. For this end, the research was centered on the users of a Rio de Janeiro, Brazil, college and the EXCEL and MATLAB software were used. The Fuzzy Logic was employed to assess IPod usability. The methodology presented here by is unprecedented and was developed by a 25-student study group of the above-mentioned college in their research.